Phosphorylation-induced modulation of pNBC1 function: distinct roles for the amino- and carboxy-termini - Gross, E (Blackwell Science Inc, 2003)
The human NBC1 (SLC4A4) gene encodes the electrogenic sodium bicarbonate cotransporters kNBC1 and pNBC1, which are highly expressed in the kidney and pancreas, respectively. The HCO(3)(−):Na(+) stoichiometry of these cotransporters is an important determinant of the direction of ion flux. Recently we showed in a mouse proximal tubule (mPCT) cell line expressing kNBC1, that 8-Br-cAMP shifts the stoichiometry of the cotransporter from 3:1 to 2:1 via protein kinase A (PKA)-dependent phosphorylation of Ser(982). pNBC1 has the identical carboxy-terminal consensus phosphorylation PKA site (KKGS(1026)), and an additional site in its amino-terminus (KRKT(49)). In this study we determined the potential role of these sites in regulating the function of pNBC1. The results demonstrated that in mPCT cells expressing pNBC1, PKA-dependent phosphorylation of Ser(1026) following 8-Br-cAMP treatment shifted the stoichiometry from 3:1 to 2:1. The effect was electrostatic in nature as replacing Ser(1026) with Asp resulted in a similar stoichiometry shift. In addition to shifting the stoichiometry, 8-Br-cAMP caused a significant increase in the 4,4′-dinitrostilbene-2,2′-disulfonic acid (DNDS)-sensitive basolateral membrane conductance (G(DS)) of cells expressing pNBC1, but not kNBC1. Although, the effect did not involve phosphorylation of Thr(49), which was endogenously phosphorylated, replacing this residue with Asp or Ala abolished the 8-Br-cAMP-induced increase in G(DS). In the mPEC pancreatic duct cell line, where endogenous pNBC1 functions with a HCO(3)(−):Na(+) stoichiometry of 2:1, 8-Br-cAMP increased G(DS) by ∼90 % without altering the stoichiometry or inducing phosphorylation of the cotransporter. The results demonstrate that phosphorylation of Ser(1026) mediates the cAMP-dependent shift in the stoichiometry of pNBC1, whereas Thr(49) plays an essential role in the cAMP-induced increase in G(DS).